PERKEMBANGAN JIWA AGAMA PADA ANAK (ANALISIS KAJIAN DAN PEMIKIRAN DALAM PSIKOLOGI AGAMA) - Rossi Delta Fitrianah (Al Fitrah: Journal Of Early Childhood Islamic Education, 2019)
The process of development of religious life may be quite unique compared to the development aspects of aspects in other human beings. If visualized in graphic form, then aspects of human life aspects such as physical, intellectual, social and so on generally experience improvement in childhood until adolescence or adult Childhood is a period in which an individual begins to interact with other individuals, during this period is actually a golden period in which a person is introduced religion, because this time a child who is not too critical in the sense of what each of his parents will receive it. The influence of the environment especially the family is very dominant for the development of one's religious. A child raised in a religious family will be more likely to develop more religious than the one who does not. A child born into a Muslim family, automatically possessed by a religious instict, develops in an Islamic tradition and is likely to become a Muslim. Keywords: Development of the religious psyche, Child